Diversity of mung bean insect pests and their natural enemies in farmers’ fields in East Java, Indonesia - SRI WAHYUNI INDIATI; BEJO BEJO; M. RAHAYU (Society for Indonesian Biodiversity, 2017)
Indiati SW, Bejo, Rahayu M. 2017. Diversity of mung bean insect pests and their natural enemies in farmers’ fields in East Java, Indonesia. Biodiversitas 18: 1300-1307. A survey was conducted from June to September in 2016 in mung bean fields in East Java. The objectives of this survey were to identify the mung bean pests that were present, and to identify potential natural enemies of these pests at each location. Insect pests recorded in low numbers in all fields surveyed were bean fly (Ophiomyia phaseoli), thrips and grasshoppers. Pod sucking bugs (Nezara viridula, Piezodorus hybneri, and Riptortus linearis) were found in all fields in all months. The population densities of pod sucking bugs were relatively high, and represent a major threat to mung beans in Indonesia.White flies (Bemicia tabaci) and leafhoppers (Empoasca spp.) were found in low numbers in all fields surveyed during the August-September period. Several new pests of mung bean were recorded in this survey: the leaf beetle (Megacopta cribraria) was recorded in fields in the villages of Pungkurlawas, Brondong, Lamongan; and pod boring weevils (Apion clavipes, Curculionoidae) were found in high numbers in Madiun and Nganjuk, resulting in significant damage to mung bean pods. Natural enemies of insect pests recorded during the survey were spiders, dragonflies, Hymenoptera (Braconidae and Trichogrammatidae), Diptera (Tachinidae and Syrphidae), and Coleoptera (Coccinellidae and Paederus fuscipes). Natural enemies - spider and Coccinella predators - were present in low numbers in all fields surveyed, although Coccinella predators were not present in Lamongan.